Dorm room dealers: drugs and the privileges of race and class - Mohamed, A. Rafik (Lynne Rienner Publishers, Inc, 2010)
Overlooked illegal markets: dealing dope, college style -- The primary market: dealing marijuana, cocaine, and party drugs -- Why rich kids sell street street drugs: wankstaz, wannabes, and capitalists in training -- The emerging market: peddling prescription drugs -- How student dealers rationalize crime: mental gymnastics -- Perceived and actual risks for college dealers: un-risky business -- Conclusions and epilogue: no dreams deferred